(untitled) (Academicia Globe: Inderscience Research, 2021)
Drought-tolerant, salt-tolerant phyto-reclamation plants such as Maksar and White corn should be planted as secondary crops to prevent the devastation of grain-free areas and the deterioration of the reclamation status of these areas. We think these are good results. For example, white corn can be harvested as a minor crop while maintaining good soil moisture until the fall months and reducing soil salinity.